Brucellosis infection complicated with myelitis: a case report and literature review - Ma, Xiaoyu; Wang, Ying; Wu, Qiong; Ma, Xiaomei; Wang, Qiang; Guo, Qinghong (Frontiers in Cellular and Infection Microbiology, 2024)
Gram-negative coccus a facultative intracellular pathogen. Neurobrucellosis has an incidence rate of 3-7% among all patients with brucellosis, while spinal cord involvement is rare and carries a significant mortality risk. This report describes a case of brucellosis myelitis in a 55-year-old male patient who presented with recurrent paralysis, incontinence, and damage to the visual and auditory nerves. The diagnosis of neurobrucellosis involves a serum tube agglutination test, cerebrospinal fluid analysis, a physical examination of the nervous system, and a comprehensive review of the patient's medical history. The presence of brucellosis was confirmed in cerebrospinal fluid using MetaCAP TM sequencing. Treatment with a combination of rifampicin, doxycycline, ceftriaxone sodium, amikacin, compound brain peptide ganglioside, and dexamethasone resulted in significant improvement of the patient's clinical symptoms and a decrease in the brucellosis sequence count in cerebrospinal fluid. For the first time, MetaCAP TM sequencing has been used to treat pathogenic microbial nucleic acids, which could be a valuable tool for early diagnosis and treatment of neurobrucellosis.